2020
DOI: 10.1016/j.ijid.2020.04.079
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in IL-10 influences the progression of hepatitis B infection

Abstract: The outcomes of hepatitis B virus (HBV) infection vary substantially among affected individuals, providing evidence of the role of host genetic background in the susceptibility to HBV persistence and the dynamics of liver injury progression to cirrhosis and hepatocellular carcinoma (HCC). Methods: Six single-nucleotide polymorphisms within the interleukin 10 gene (IL10) were genotyped by MALDI-TOF mass spectrometry in 857 patients with chronic HBV infection (CHB), 48 patients with resolved HBV infection, and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 25 publications
(30 reference statements)
0
10
1
Order By: Relevance
“…29 Furthermore, the ATAC haplotype was reported to be associated with treatment-induced HBsAg and less severe liver injury. 30 This is in contrast to the present study, where the IL-10 rs1800896 AG/GG genotypes are associated with spontaneous HBsAg SC and with the development of IC in female white European patients. Female patients carrying the favorable variants had almost twofold higher chances to spontaneously clear the virus or to convert to inactive carriers, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…29 Furthermore, the ATAC haplotype was reported to be associated with treatment-induced HBsAg and less severe liver injury. 30 This is in contrast to the present study, where the IL-10 rs1800896 AG/GG genotypes are associated with spontaneous HBsAg SC and with the development of IC in female white European patients. Female patients carrying the favorable variants had almost twofold higher chances to spontaneously clear the virus or to convert to inactive carriers, respectively.…”
Section: Discussioncontrasting
confidence: 99%
“…IL-10 is a key regulatory component of the immune response that suppresses T-cell proliferation, antigen-presenting cell functions and production of pro-inflammatory cytokines during the recovery stage following infection, in order to limit the inflammation-mediated tissue damage 34 . Previous studies have reported the effect of IL10 polymorphisms on the susceptibility to human immunodeficiency virus infection 35 , 36 or the risk of HBV-induced liver damage and progression to chronicity 37 . A large proportion of the interindividual variability observed in the production of human IL-10 is attributable to genetic variation in the highly polymorphic promoter region of the IL10 gene, where the rs1800872 SNP is located 38 .…”
Section: Discusionmentioning
confidence: 99%
“…Several studies have found that genetic variants on the human leucocyte antigen (HLA)-DP gene are associated with HBsAg-seroclearance during the natural history of infection [ 64 ] or during treatment with NA [ 65 ], which seems to be consistent across different populations [ 66 ]. Other polymorphisms on genes linked to immunological function, such as the toll-like receptor 3 [ 67 ], interleukin 10 [ 68 ], and T-cell immunoglobulin and mucin domain-containing molecule 3 genes [ 69 ], have also shown to be linked to the natural progression of HBV infection and are less consistently studied [ 66 ]. There have been very few studies examining the role of genetic polymorphisms on HBsAg-seroclearance in HIV-HBV co-infected individuals, apart from the IL28B haplotype showing no association [ 70 ].…”
Section: Determinants Of Functional Cure During Treated Hiv-hbv Co-infectionmentioning
confidence: 99%